(untitled) (Global Journal of Human-Social Science, 2021)
The teaching methods of various subjects should not only meet the inner needs of students, but also conform to the objective laws of external development. After repeated research and experimentation, we found that the "guided learning method" implemented with a "four-step procedure" can better solve this problem. On this basis, we can achieve a high degree of integration of "teaching" and "learning", a high degree of integration of lesson plan, textbooks, assignments and examination papers, a high degree of integration of teaching methods of various disciplines, and a high degree of integration of many teaching steps such as explanation, practice, consolidation and review. The role and power of this "high level of integration" All kinds of effects should not be underestimated. With the "high level of integration", it is easy to knock on the door of simple, efficient and effective teaching and learning, thereby making the education to step on a healthy track.